Podocyte-specific overexpression of human angiotensin-converting enzyme 2 attenuates diabetic nephropathy in mice - Nadarajah, Renisha; Milagres, Rosangela; Dilauro, Marc; Gutsol, Alex; Xiao, Fengxia; Zimpelmann, Joseph; Kennedy, Chris; Wysocki, Jan; Batlle, Daniel; Burns, Kevin D. (Université d'Ottawa | University of Ottawa, 2012)
Angiotensin-converting enzyme 2 (ACE2) degrades angiotensin II to angiotensin-(1–7) and is expressed in podocytes. Here we overexpressed ACE2 in podocytes in experimental diabetic nephropathy using transgenic methods where a nephrin promoter drove the expression of human ACE2. Glomeruli from these mice had significantly increased mRNA, protein, and activity of ACE2 compared to wild-type mice. Male mice were treated with streptozotocin to induce diabetes. After 16 weeks, there was no significant difference in plasma glucose levels between wild-type and transgenic diabetic mice. Urinary albumin was significantly increased in wild-type diabetic mice at 4 weeks, whereas albuminuria in transgenic diabetic mice did not differ from wild-type nondiabetic mice. However, this effect was transient and by 16 weeks both transgenic and nontransgenic diabetic mice had similar rates of proteinuria. Compared to wild-type diabetic mice, transgenic diabetic mice had an attenuated increase in mesangial area, decreased glomerular area, and a blunted decrease in nephrin expression. Podocyte numbers decreased in wild-type diabetic mice at 16 weeks, but were unaffected in transgenic diabetic mice. At 8 weeks, kidney cortical expression of transforming growth factor-β1 was significantly inhibited in transgenic diabetic mice as compared to wild-type diabetic mice. Thus, the podocyte-specific overexpression of human ACE2 transiently attenuates the development of diabetic nephropathy.
Keywords: ACE2; albuminuria; angiotensin; apoptosis; diabetes; podocyte